2005
DOI: 10.1128/iai.73.6.3734-3739.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protein Microarray for Profiling Antibody Responses to Yersinia pestis Live Vaccine

Abstract: A protein microarray representing 149 Yersinia pestis proteins was developed to profile antibody responses in EV76-immunized rabbits. Antibodies to 50 proteins were detected. There are 11 proteins besides F1 and V antigens to which the predominant antibody response occurred, and these proteins show promise for further evaluation as candidates for subunit vaccines and/or diagnostic antigens.Plague, one of the most dangerous diseases, is caused by Yersinia pestis. The increasing possibility of antibiotic-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 38 publications
1
73
0
2
Order By: Relevance
“…Indeed, a recent protein microarray study showed that the Y. pestis-specific genes YPO0388, YO2090 and YPO2093 encoded proteins that induced significant antibody response in the immunized rabbit. 77 These results yield clues about the role of these genes in pathogenicity and immunity, and beg for further investigation into these possibilities and for the potential use of these immunogens as vaccine candidates.…”
Section: Comparative Genomic Studiesmentioning
confidence: 99%
“…Indeed, a recent protein microarray study showed that the Y. pestis-specific genes YPO0388, YO2090 and YPO2093 encoded proteins that induced significant antibody response in the immunized rabbit. 77 These results yield clues about the role of these genes in pathogenicity and immunity, and beg for further investigation into these possibilities and for the potential use of these immunogens as vaccine candidates.…”
Section: Comparative Genomic Studiesmentioning
confidence: 99%
“…Defined protein collections assembled from phage expression systems or purified from recombinant sources were used to detect antibody responses in the serum of ovarian (11,12), breast (13), colorectal (2), pancreatic (14), or lung (15,16) cancer patients, and some of these responses appear to have diagnostic significance. In addition, protein array tools are also useful to measure changes in antibody responses to vaccination or immunotherapies, although it has yet to be applied to the monitoring of cancer treatments (17,18). So far, studies have often concentrated either on small numbers of defined antigenic targets tested across large serum datasets, or on large numbers of proteins probed by a limited number of patient sera, likely because of prohibitive cost constraints and arduous handling of large data samples.…”
mentioning
confidence: 99%
“…They produced antigen microarrays with 430 different proteins and overlapping peptides spanning the whole SHIV proteome and identified eight immunodominant epitopes. Antibody responses of immunized rabbits to Yersinia pestis vaccine was performed by Li and colleagues [168]. They applied protein microarrays harboring 149 Yersinia pestis proteins and were able to detect 13 imunogenic proteins.…”
Section: Applicationsmentioning
confidence: 99%